Application of Omics Tools in Designing and Monitoring Marine Protected Areas For a Sustainable Blue Economy - Jeffery, Nicholas W.; Lehnert, Sarah J.; Kess, Tony; Layton, Kara K. S.; Wringe, Brendan F.; Stanley, Ryan R.E. (Frontiers in Genetics, 2022)
A key component of the global blue economy strategy is the sustainable extraction of marine resources and conservation of marine environments through networks of Marine Protected Areas. Connectivity and representativity are essential factors that underlie successful implementation of MPA networks, which can safeguard biological diversity, ecosystem function, and ultimately support the blue economy strategy by balancing ocean use with conservation. New ‘big data’ omics approaches, including, genomics and transcriptomics, are becoming essential tools for the development and maintenance of MPA networks. Current molecular omics techniques, including population-scale genome sequencing, have direct applications for assessing population connectivity and for evaluating how genetic variation is represented within and among MPAs. Effective baseline characterisation and long-term, scalable, and comprehensive monitoring are essential for successful MPA management, and omics approaches hold great promise to characterize the full range of marine life, spanning the microbiome to megafauna across a range of environmental conditions (shallow sea to the deep ocean). Omics tools, such as eDNA metabarcoding can provide a cost-effective basis for biodiversity monitoring in large and remote conservation areas. Here we provide an overview of current omics applications for conservation planning and monitoring, with a focus on metabarcoding, metagenomics, and population genomics. Emerging approaches, including whole genome sequencing, characterisation of genomic architecture, epigenomics, and genomic vulnerability to climate change are also reviewed. We demonstrate that the operationalisation of omics tools can enhance the design, monitoring, and management of MPAs and thus will play an important role in a modern and comprehensive blue economy strategy.